Business Innovation Development: Obstacles and Opportunities - Valentinavičius, Stasys (Ekonomika, 2006)
Fast economic growth is closely interrelated with renovation of industrial technologies. implementation of novelties and a rapid development of business innovation. Based on the European Union (EU) experience, identifying the key obstacles and opportunities for business development and growth becomes increasingly important for Lithuania. Therefore. before delving into daily business practices. the theoretical principles of innovation development need to be thoroughly discussed. The article examines an interrelation between innovation and economic competitiveness, the methodology of business innovation concept, the importance of development acceleration and financial support as well as the strategic objectives. The article offers a comparative analysis of innovation funding in Lithuania and other EU countries. Innovation survey is based on official reports of Lithuanian Department of Statistics, European Commission, Organization for Economic Co-operation and Development and other establishments. It is supported by research findings and reviews of different authors. Lithuanian strategies and legal acts. Methods of statistical data comparative analysis and content analysis of scientific literature and publications were also applied in the survey. After joining the European Union, one of the most important topics became raising the competitiveness of Lithuanian economy to attain the long-term objectives set out by the Lisbon Strategy. It broadly aims at making “the EU the world’s most dynamic and competitive economy” by the 2010 deadline. The Lisbon Strategy is heavily based on the fast growth of quantitative and qualitative scientific research, economic potential and development of business innovation. Despite the fact that the Lithuanian economy is developing faster than on average the EU does, the backwardness of the country is obvious. One of such areas is technological and innovation development. The economy is still occupied by the conventional orientation towards technologies and markets. The survey has shown that the biggest obstacle for business innovation development is the lack of capital which is supposed to be invested into development of ground breaking, however unprofitable products and management systems, which would result in a bigger efficiency and innovativeness only in a long run. Funding of business innovation as a risktaking activity is not attractive to investors due to permanent control and opportunity costs, which are substantial even if innovation is managed at a small scale. Such widely operating innovat ion funding sources as “Angel Investors” or “Seed Capital” in Western economies are not yet present in Lithuania. In the meanwhile there are just a few risk capital funds in Lithuania, which usually show interest in big-scale projects due to the fact that the risk capital market goes through a fierce competition. Most frequently only the best project proposals receive funding, out of which just a few turn into a success and attain fast development. For example, in 2001 as little as 17% of officially operating risk capital in Europe was assigned to primary business investments. The Risk Capital Action Plan identifies six categories of obstacles, which prevent risk capital market development in Europe: fragmentation of markets; legal regulations; taxation; small presence of SME in hi-tech area; human resources, culture. Having made a review of the current situation in Lithuania and the European Union, the following sources of business innovation funding can be identified: the European Structural Funds, European Union innovation project programs; international funding corporations; investor associations; risk capital companies; mezzanine; “Angel Investors”; guarantee funds and banks. Innovation implementation in Lithuania in comparison with the EU is very different in terms of funding. According to data of the Lithuanian Department of Statistics, Research and Development (R&D) by sectors in 2003 were funded as follows: funds of business enterprises - 16.7%, government funds - 64.6%; foreign funds - 13.8%; university funds - 4.8%; private non-profit sector funds - 0.1%. Taking into account the objective of Lisbon Strategy, which implies that 2/3 of business innovation should come from the business sector aiming to attain the EU average, Lithuanian business initiative should be prompted better in these regards. Taking into account the present Lithuanian input into R&D (0.68% of GDP in 2003 and 0.76% GDP in 2004), support of Structural Funds of the current and coming periods, general economy development trends, in the National Lisbon Action Program it is admitted that Lithuania will have difficulties in allotting 3% of gross domestic expenditures, and especially from the business sector, for research and development by 2010, as it is averagely targeted in the EU. Nevertheless, the author expects that in any case, attention, joint efforts and funding of Lithuanian government institutions, business and educational organizations into R&D should be much more substantial than it is set in the Program, and they should attain no less than 2.5% of GDP and from the business sector 1.2% of GDP. While conducting PAP! (paper and pencil interviews) in Lithuanian enterprises on innovation activities, respondents were asked to indicate financial funds they use. The response rate reached 60%. Nearly all respondents have stated that companies first of all employ their own resources and profits. In several instances there were mentioned banks, stock capital and access to partner resources. Such a reserved funding shows that in fact innovation activities are quite passive in Lithuania due to the lack of financial resources. There were indicated a few most risktaking ways of projects’ funding: high interest rates, trading in property (which corresponds to bank lawns or mezzanine funding), involvement of third parties into business performance, as well as high standards for productivity and profitability (which corresponds to mezzanine, risk capital or “Angel Investors” funds), stock emission and sales to third parties under condition that later on company shares will be acquired at a market price (which corresponds to risk capital and “Angel Investors” funds). Nevertheless, 53% of respondents have indicated that they don’t plan any new projects as long as they haven it generated enough of needed resources. As little as two respondents would consider stock emission and credits at high interest rates. This shows that companies in Lithuania still experience a fear of taking credits, future uncertainty and a too narrow choice of financial instruments. The experience of developed economies imposes that one of the main preconditions of economical growth in Lithuania is development of future technologies and innovation. This asks for a well-coordinated system of actions to accelerate innovation; to provide necessary information, consultancy and financial support not only to scientific research organizations and the business sector, but also to establishments of education. It is important to acknowledge on the statewide scale that EU Structural Funds, which now raise big expectations, will support Lithuania to the extent as they do now on temporary basis only. For the Lithuanian economy to sustain its competitiveness in the international arena in the future. in parallel efforts should be made to develop a system of incentives for an effective risk capital market and business innovation growth.